Evans Syndrome at Childhood-Onset Systemic Lupus Erythematosus Diagnosis: A Large Multicenter Study - Lube, Gabriella E.; Ferriani, Mariana Paes Leme; Campos, Lucia Maria Arruda; Terreri, Maria Teresa; Bonfá, Eloisa; Magalhães, Claudia Saad [UNESP]; Aikawa, Nadia Emi; Piotto, Daniela Petry; Peracchi, Octavio Augusto Bedin; dos Santos, Maria Carolina; Appenzeller, Simone; Ferriani, Virginia Paes Leme; et al. (Wiley, 2016)
Background: Evans syndrome (ES) in childhood-onset systemic lupus erythematosus (cSLE) patients has been rarely reported and limited to small populations. Procedures: A retrospective multicenter cohort study (Brazilian cSLE group) was performed in 10 Pediatric Rheumatology services including 850 patients with cSLE. ES was assessed at disease diagnosis and defined by the combination of immune thrombocytopenia and autoimmune hemolytic anemia. Results: ES was observed in 11 of 850 (1.3%) cSLE patients. The majority of them had hemorrhagic manifestations (91%) and active disease (82%). All patients with ES were hospitalized and none died. Comparisons of cSLE patients with and without ES at diagnosis revealed similar frequencies of female gender, multiorgan involvement, autoantibodies profile, and low complement (P > 0.05). Patients with ES had a lower frequency of malar rash (9% vs. 53%, P = 0.003) and musculoskeletal involvement (18% vs. 69%, P = 0.001) than those without this complication. The frequencies of intravenous methylprednisolone (82% vs. 43%, P = 0.013) and intravenous immunoglobulin use (64% vs. 3%, P < 0.0001) were significantly higher in the ES group, with similar current prednisone dose between groups (1.1 [0.76-1.5] vs. 1.0 mg/kg/day [0-30], P = 0.195). Conclusions: Our large multicenter study identified ES as a rare and severe initial manifestation of active cSLE with good outcome. Diagnosis is challenging due to the lack of typical signs and symptoms of lupus and the requirement to exclude infection and primary immunodeficiency.
Keywords: Childhood-onset systemic lupus erythematosus; Evans syndrome; Multicenter study